THE INFLUENCE OF CEO CHARACTERISTICS ON COMPANY PERFORMANCE WITH INSTITUTIONAL OWNERSHIP AS A MODERATING VARIABLE - Arif Nasution, Abdillah; Nurina, Lia; Suwarni, Wa Ode; Purnamasari, Eva; Siregar, Nurganda (ITB AAS Indonesia Surakarta, 2024)
ABSTRACT This research is quantitative research with an exploratory approach. The data used in this research is secondary data that researchers obtained from the Indonesian Stock Exchange. The data collected comes from manufacturing companies on the Stock Exchange. The collected data was analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the CEO Charactirstic variable can have a positive relationship and a significant influence on Company Performance and the Institutional Ownership variable can moderate the influence of the Company Performance variable on Company Performance. This is because the P-Values value of the CEO Characteristic variable can have a positive relationship towards Company Performance which is below the 0.05 significance level, namely 0.004, and the P-Values value of the Institutional Ownership moderating variable can strengthen the influence of the CEO Characteristic variable on Company Performance, which is below 0.05, namely 0,000. This is because the CEO has an important role in expanding networks, being a negotiator, issuing policies, and so on which can improve employees which ultimately can influence employee performance. Apart from that, Institutional Ownership can give the CEO freedom in determining policies and so on. Thus, the first and second hypotheses in this study can be accepted. Keywords: Ceo Characteristics, Company Performance , Institutional Ownership